Taxonomic revision of the cleptoparasitic bee genus Epiclopus Spinola, 1851 (Hymenoptera: Apidae: Ericrocidini) - Vivallo, Felipe (Zootaxa, 2014)
A taxonomic revision of the cleptoparasitic bee genus Epiclopus Spinola is presented. The following species are recognized: Epiclopus gayi Spinola, E. lendlianus (Friese), E. wagenknechti (Ruiz) and E. ecphorus new species from northern Chile. Floral associations, hosts, distribution records and diagnoses of both sexes based on type specimens, are given. An identification key, illustrations and an updated catalogue of the species are provided. In addition, a neotype for Mesonychium wagenknechti and lectotypes for Melissa (Epiclopus) gayi albescens Friese and M. lendliana are also designated.